Protection and communication for a 230 kV transmission line using a pilot overreaching transfer tripping (POTT) scheme - Escalante De Leon, Lazaro Samuel (Kansas State University, 2013)
New applications are continuously emerging in the ever-changing field of power systems in the United States and throughout the world, consequently causing new pressures on grid performance. Because power system protection is a fundamental aspect of the system, their operation must be addressed when a system is under high stress or when a high demand of energy is required. An extreme example is the transmission protection of a system because it transports large amounts of power. Transmission lines in a power system are frequently exposed to faults and generally protected by distance relays. If a faulted segment of transmission lines is not cleared in a short period of time, the system becomes unstable. The basic function of distance protection is to detect faults in buses, transmission lines, or substations and isolate them based on voltage and current measurements. Power system protection has previously focused on matching automation and control technologies to system performance needs. This report focuses on project activities that run simulations to determine settings for a protective relay for pilot overreaching transfer tripping and then test the settings using hardware equipment for various scenarios. The first set of scenarios consists of five faults in the system; two faults are in the protected line, and the remaining faults are outside the protective line. The second set of scenarios consists of instrument transformer failures in which the current transformer (CT) of one relay fails to operate while the other relay is fully operational. The second scenario consists of a failure of the voltage transformer (VT) of one relay while the other relay remains fully operational. Finally, the third and fourth scenarios consist of the failure of both CTs and VTs for each relay.
Keywords: Power system protection; Electrical Engineering (0544)